Radya Pustaka Museum As the Preservation Of Surakarta Cultural Heritage From 2008 - 2018 - Vista Anindya Kusuma; Marjono Marjono; Sumarjono Sumarjono (History Education, University of Jember, 2020)
Radya Pustaka Museum was founded by KRA Sosrodiningrat IV on October 28, 1890, which aims to preserve the art of Javanese culture. The management of the Radya Library museum from 2008 - 2018 was performed by the committee and Technical Unit Implementation as well as support from the Surakarta City Government. Efforts to preserve cultural heritage objects carried out by managers of the Radya Library Library must be based on regulations set by the government. Method this study enganger of historical study. The results of the research show that since 2008 - 2018 the Radya Library library has undergone two changes of management, namely since 2008 the museum was managed by a committee with the assistance of a grant from the Surakarta City government and in 2016 - 2018 the museum has been transferred under the control of the Surakarta Cultural Service UPT museum and operational funds are obtained from the Surakarta City Government Budget. Preservation of Cultural Heritage in the Radya Pustaka museum is based on the Law on Cultural Heritage No. 11 of 2010. The museum preserves cultural heritage was encouraged by the existence of an ancient manuscript of the Kasunanan palace which was not maintained and to grow interest for cultural heritage to the community. Since 2008 - 2018 Radya Library management was managed by the committee and Technical Unit Implementation. Efforts to preserve cultural heritage in the Radya Pustaka museum by implementing protection, development and utilization of cultural heritage. Keywords: Management, Radya Pustaka, Preservation.